2019
DOI: 10.1093/ee/nvz007
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Pesticide Residues to a Plant Genus Using Palynology in Pollen Trapped from Honey Bees (Hymenoptera: Apidae) at Ornamental Plant Nurseries

Abstract: Worldwide studies have used the technique of pollen trapping, collecting pollen loads from returning honey bee ( Apis mellifera L.) (Hymenoptera: Apidae) foragers, to evaluate the exposure of honey bees to pesticides through pollen and as a biomonitoring tool. Typically, these surveys have found frequent contamination of pollen with multiple pesticides, with most of the estimated risk of acute oral toxicity to honey bees coming from insecticides. In our survey of pesticides in trapped po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…(2020) 10:831 | https://doi.org/10.1038/s41598-020-57858-2 www.nature.com/scientificreports www.nature.com/scientificreports/ Methods Study sites and sampling regime. The current study used samples that were previously analyzed for pesticide residues and reported in 38 . The study sites and pollen sampling scheme are described in detail in 38 , and briefly described here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2020) 10:831 | https://doi.org/10.1038/s41598-020-57858-2 www.nature.com/scientificreports www.nature.com/scientificreports/ Methods Study sites and sampling regime. The current study used samples that were previously analyzed for pesticide residues and reported in 38 . The study sites and pollen sampling scheme are described in detail in 38 , and briefly described here.…”
Section: Resultsmentioning
confidence: 99%
“…The current study used samples that were previously analyzed for pesticide residues and reported in 38 . The study sites and pollen sampling scheme are described in detail in 38 , and briefly described here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of papers have attempted to address this by translating the HQ threshold into a percentage of the LD 50 based on daily consumption of pollen, e.g. a HQ of 50, 100 or 1000 corresponding to 0.05%, 0.1% or 1% of the acute oral LD 50 , respectively, 6–9 but provide no evidence to support the importance of the cited percentage of the acute oral LD 50 . Taking this further, the percentage of the acute (single dose) LD 50 represented by the HQ has been increased ten‐fold by using estimates of cumulative pollen consumption by nurse bees over a 10‐day period, i.e.…”
Section: Erroneous Conclusion Resulting From the Use Of The Hazard Quotient To Evaluate Residue Data From Pollen And Nectarmentioning
confidence: 99%
“…One strength of these data is their standardized collection and thus ease of use for comparison across compounds in examining collective (or additive) effects. To do this, we calculated the hazard quotient for each compound, by dividing the detected concentration by the LD 50 , and then summed this across all compounds in each sample (Stoner et al, 2019). This approach has an important drawback in that assumes a linear relationship between concentration and effect, which is often not realized, and then propagates this across all compounds in each sample.…”
Section: Methodsmentioning
confidence: 99%